2018
DOI: 10.3390/w10060809
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Source Uncertainty Analysis in Simulating Floodplain Inundation under Climate Change

Abstract: Floodplains are highly complex and dynamic systems in terms of their hydrology. Thus, they harbor highly specialized floodplain plant species depending on different inundation characteristics. Climate change will most likely alter those characteristics. This study investigates the potential impact of climate change on the inundation characteristics of a floodplain of the Rhine River in Hesse, Germany. We report on the cascading uncertainty introduced through climate projections, climate model structure, and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…The use of hydrological models for assessing changes in floods, especially for future projections, adds another dimension of uncertainty on top of uncertainty in the driving climate projections, including emissions scenarios, and in the driving climate models (both RCMs and GCMs) (Arnell and Gosling, 2016;Hundecha et al, 2016;Krysanova et al, 2017). The differences in hydrological models (Roudier et al, 2016;Thober et al, 2018), as well as postprocessing of climate model output for the hydrological models (Muerth et al, 2013;Maier et al, 2018), add to uncertainty for flood projections.…”
Section: Model Evaluationmentioning
confidence: 99%
“…The use of hydrological models for assessing changes in floods, especially for future projections, adds another dimension of uncertainty on top of uncertainty in the driving climate projections, including emissions scenarios, and in the driving climate models (both RCMs and GCMs) (Arnell and Gosling, 2016;Hundecha et al, 2016;Krysanova et al, 2017). The differences in hydrological models (Roudier et al, 2016;Thober et al, 2018), as well as postprocessing of climate model output for the hydrological models (Muerth et al, 2013;Maier et al, 2018), add to uncertainty for flood projections.…”
Section: Model Evaluationmentioning
confidence: 99%
“…For example, it is possible to run the model with different land use change scenarios (Maier, Breuer, Chamorro, Kraft, & Houska, 2018). Our habitat model is capable of simulating changes in vegetation cover (selection of species and changes in land management), morphological characteristics (floodplain reconstruction, construction of embankments, and river regulation), and climate (precipitation amounts and seasonal patterns, and temperature affecting evapotranspiration).…”
Section: Conclusion and Further Applicationsmentioning
confidence: 99%
“…The study area as shown in Figure 2 is located in Northeast China. The catchment is about 2085 km 2 . The Biliu River reservoir plays a significant role in supplying water to nearby big cities.…”
Section: Study Areamentioning
confidence: 99%
“…Uncertainty analysis is important when simulating runoff because it is difficult for hydrological models to reflect the hydrological process perfectly. Outputs of the Global Climate Models (GCMs) are the most effective data to represent future climate conditions and are widely used to study future hydrological responses to the impact of climate change [1][2][3]. Generally, hydrological models are driven by future climate data from GCMs, and then the projected future runoff is compared with historically measured runoff to analyze the runoff's response to climate change.…”
Section: Introductionmentioning
confidence: 99%